AB1284 Preliminary data of vaccination status, post vaccination immunity and latent tuberculosis in patients with chronic inflammatory disease in a rheumatology consultation in st rafael's hospital in barcelona. (12th June 2018) - Erra, A.; Borrell, H.; López, L.; Martinez, X.
Abstract : Background: Chronic inflammatory diseases (CID)(Rheumatoid arthritis(RA), Psoriatic arthritis(PsA) and ankylosing spondylitis(AS) are treated with disease modifying antirheumatic drugs(DMARDs). The most common adverse events are infections so an adequate vaccination is necessary before starting these treatments Objectives: Determine the vaccination status, post-vaccination response and presence of latent tuberculosis(TB) in patients(pts)with CID Methods: Before treatment with DMARDs, hepatitis C virus(HCV) antibodies, hepatitis B(HBV)surface antigen are determined. Following the guideline of Spanish Society of Rheumatology, before start a biological treatment(BT), latent tuberculosis(TB)screening is done by PPD and booster test. We and Preventive Medicine Department(PMD) of Vall Hebron Hospital(VHH) stablished vaccination protocol for pts with CID treated with DMARDs or/and BT:anti pneumococcal vaccination, virus serological status(varicella zoster IgG, measles IgG, anti-hepatitis A IgG, HBV surface antigen, HBV anti-surface antigen, HBV anti-core antigen and anti-HCV) and quantiferon(QT) test by assessment latent TB. Vaccines were administered depending on the above tests such as the determination of the post-vaccination HBV serology. Positive QT pts were referred to Infectious Diseases Department of VHH and received Isoniazid for 6 months Results: From October 2016 to November 2017, 123 pts with CID(including new onset and chronic disease) were referred to PMD. The pts were classified:81 RA(16 BT/65 DMARDs);25 PsA(9 BT/16 DMARDs), 13 AS(10 BT/3 DMARDs), 5 others(2 BT/3 DMARDS):2 juvenile idiopathic arthritis, 1 reactive arthritis, 1 monoarthritis and 1 polymyalgia rheumatica. Pts with BT were treated:14 RA with combined therapy(CT) and 2 with monotherapy;9 AS with monotherapy and 1 with CT, 2 PsA with monotherapy and 7 with CT.19 pts had QT(+):2 had previously PPD(-);3 had previously PPD(+) and it was unknown in 14. Pts with PPD(+) and QT(+)(n=4), all of them who received BT(n=3) had been treated with isoniazid. The patient treated with DMARDs didn't received it. Pts QT(+) and previous PPD(-)(n=2):1 with BT for years and never before had been treated with isoniazid, so this treatment was started. The other with DMARDs started treatment with isoniazid as she was going to start BT in a short time. The rest of the pts QT(+)(n=14) didn't have a previous PPD(all DMARDs).11 received prophylaxis with isoniazid and 3 didn't, because they didn't require BT soon.19% of pts had positive HBV's serology, so they didn't receive HBV vaccination. 81%(n=100) had a negative anti-Ag surface HBV.92% of them received the vaccination, and from them, 9% didn't develop immunologic response so they needed revaccination(3 received TC BT-DMARDs and 5 DMARDs in monotherapy).42% developed immunologic response and in 49% we are waiting for the results.16% had a negative HAV's serology and all of them received the vaccination Conclusions: The quantiferon can detect latent TB in patients with negative PPD and booster. Most patients need vaccination to HBV. Check the immunity from HBV is necessary after vaccination to know if they need revaccination. In our preliminary data we have observed absence of immunity to HBV in patients who are treated with BT (with CT) and also in patients who are treated with synthetic DMARDs. Disclosure of Interest: None declared